2005
DOI: 10.1111/j.1551-2916.2005.00780.x
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Carbide‐Derived Carbon on β‐Silicon Carbide Whiskers

Abstract: Carbon was synthesized on b-SiC whiskers by extraction of Si atoms from SiC. In this study, three different elevated temperature extraction methods were used to remove Si atoms from SiC: treatments in either Cl 2 or HCl and vacuum decomposition. In all chlorination experiments and vacuum treatment at 17001C, carbon preserved the original shape of SiC whiskers. At higher temperatures (20001C), vacuum decomposition led to a distortion in the shape of the whiskers. High-resolution transmission electron microscopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(50 citation statements)
references
References 29 publications
(43 reference statements)
3
43
0
2
Order By: Relevance
“…108,[110][111][112][113][114] For EDLC applications, CDC is generally produced by treatment of carbides in a chlorine gas. In the case of binary carbides a simplified reaction can be written as: MeC x + 0.5Cl 2 = MeCl y + xC, where Me could be Al, 115 B, [116][117][118][119] Ca, 120 Cr, 121 Mo, 122,123 Si, 13,114,[124][125][126][127][128] Ti, 114,[129][130][131][132] V, 133 W, 134 Zr, 111,135 or other carbide-forming metals. In addition, CDC with enhanced pore volume could be produced using ternary carbides, such as Ti 2 AlC, Ti 3 AlC 2 , and Ti 3 SiC 2.…”
Section: Carbide Derived Carbonsmentioning
confidence: 99%
“…108,[110][111][112][113][114] For EDLC applications, CDC is generally produced by treatment of carbides in a chlorine gas. In the case of binary carbides a simplified reaction can be written as: MeC x + 0.5Cl 2 = MeCl y + xC, where Me could be Al, 115 B, [116][117][118][119] Ca, 120 Cr, 121 Mo, 122,123 Si, 13,114,[124][125][126][127][128] Ti, 114,[129][130][131][132] V, 133 W, 134 Zr, 111,135 or other carbide-forming metals. In addition, CDC with enhanced pore volume could be produced using ternary carbides, such as Ti 2 AlC, Ti 3 AlC 2 , and Ti 3 SiC 2.…”
Section: Carbide Derived Carbonsmentioning
confidence: 99%
“…In contrast to other CDC, SiCderived CDC remain amorphous up to 1200°C. [21] Changes in CDC microstructure are inherently connected to changes in pore structure. Amorphous structures formed at lower temperatures are clearly associated with uniform and relatively small pores, whereas graphitic ribbon network structures formed at higher synthesis temperatures are linked to less uniform and generally larger pores (compare Figs.…”
Section: Structure and Porositymentioning
confidence: 99%
“…It was shown previously that extraction of metals from carbides by halogens or their compounds leads to the formation of free carbon with various structures called carbide‐derived carbon (CDC) 37,38 . For SiC and β‐SiC whiskers, it has been reported that the Si component is preferentially attacked and a carbon‐rich layer builds up in the reaction with chlorine‐ or fluorine‐containing gases at temperatures >600°C 39,40 . Thus, CDC‐coated micropatterned SiC, which might be loaded with heterogeneous catalyst, can be of considerable interest for lining of reactor systems in chemical engineering to increase the performance of heterogeneous catalytic reactions.…”
Section: Resultsmentioning
confidence: 99%